2018
DOI: 10.20502/rbg.v19i1.1248
|View full text |Cite
|
Sign up to set email alerts
|

Dinâmica Do Carbono Orgânico E Processos Hidrológicos Na Escala Da Bacia Hidrográfica: Uma Revisão

Abstract: Resumo:Os processos de armazenamento e transferência de carbono orgânico (CO) em bacias hidrográfi cas são governados por interações entre processos hidrológicos e biogeoquímicos. Estudos clássicos evidenciam o papel da matéria orgânica na estabilização dos agregados do solo, propriedades físico-químicas e qualidade do solo, entretanto os mecanismos de desestabilização do carbono orgânico, armazenamento e transporte ainda são parcialmente descritos e compreendidos. Este artigo tem como objetivo apresentar uma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Dissolved Organic Carbon (DOC) is a key component of not only the global carbon cycle but also surface water quality as it connects sources of organic matter in the soil to carbon cycling and sequestration in aquatic ecosystems (Cole et al, 2007;Tranvik et al, 2009;Chaplot & Ribolzi, 2013). Thus, describing how hydrological and biogeochemical processes interact across landscapes is critical to understanding shifts in DOC concentration in shallow groundwater (GW) and streams (Siefert & Santos, 2018). Previous studies have shown that catchment functioning, in terms of the spatial and temporal variation of GW contributions to runoff generation, and DOC fl uxes can exhibit evidence of threshold-mediated and connectivity-controlled processes (McGlynn & McDonnell, 2003;Dick et al, 2015;Solomon et al, 2015), creating uncertainties about DOC spatiotemporal dynamics and their movement across landscapes to streams.…”
Section: Introductionmentioning
confidence: 99%
“…Dissolved Organic Carbon (DOC) is a key component of not only the global carbon cycle but also surface water quality as it connects sources of organic matter in the soil to carbon cycling and sequestration in aquatic ecosystems (Cole et al, 2007;Tranvik et al, 2009;Chaplot & Ribolzi, 2013). Thus, describing how hydrological and biogeochemical processes interact across landscapes is critical to understanding shifts in DOC concentration in shallow groundwater (GW) and streams (Siefert & Santos, 2018). Previous studies have shown that catchment functioning, in terms of the spatial and temporal variation of GW contributions to runoff generation, and DOC fl uxes can exhibit evidence of threshold-mediated and connectivity-controlled processes (McGlynn & McDonnell, 2003;Dick et al, 2015;Solomon et al, 2015), creating uncertainties about DOC spatiotemporal dynamics and their movement across landscapes to streams.…”
Section: Introductionmentioning
confidence: 99%